Reviews and Responses for Investigation of Point Merge Utilization Worldwide Using Opensky Network Data - Hardell, Henrik; Polishchuk, Tatiana; Smetanová, Lucie; Sáez, Raúl; Spinielli, Enrico; Trzmiel, Aymeric (Journal of Open Aviation Science, 2025)
See detailed reviews and responses in the PDF file. DOI for the original paper: https://doi.org/10.59490/joas.2025.7729